Upaya Polri Memberikan Perlindungan Hukum bagi Konsumen dalam Perjanjian Pinjaman Online Ilegal di Surakarta - Risma Dewi Hermawan; Aris Prio Agus Santoso; Kresna Agung Yudhianto (Rechtenstudent, 2023)
Technology and information are currently experiencing developments in carrying out activities in all fields with the help of technology. One of them is that online-based lending has not only positive but negative impacts, namely online loan practice services that are not registered with the Financial Services Authority (OJK) or illegal online loans which are services that have caused many cases in society. Perpetrators of illegal online loans can be subject to article 32 paragraph 1 of the Electronic Information and Transaction law. However, even though there are legal regulations, cases of illegal online loans are still found in the field. The problem in this research is how is legal protection for consumers of illegal online loans and the obstacles faced in tackling illegal online loans. This type of research is empirical juridical where data is obtained from interviews and also from literature studies. Data collection techniques were carried out by interviews at the research location after obtaining the data and then the data were analyzed qualitatively. The results of this study are that legal protection is provided for consumers in a preventive and repressive manner. Preventive legal protection is contained in Law no. 8 of 1999 concerning consumer protection, while repressive legal protection is contained in the Financial Services Authority Regulation Number 77/POJK.01/2016 of 2016 concerning Information Technology-Based Money Lending Services.